2019
DOI: 10.3390/ijerph16122229
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Psychological Mechanism of Subjective Well-Being in Migrant Workers: A Structural Equation Models Analysis

Abstract: Objective: The aim of this study was to identify the potential psychological mechanism of well-being in migrants in Shanghai, China. Methods: A cross-sectional study was conducted in 2018. First, a literature review was conducted to understand the salutogenesis of migrants in China. Then, 2573 random participants were recruited from six workplaces and public places in six districts of Shanghai. The Chinese versions of the Patient Health Questionnaire-9 (PHQ-9), the Personal Wellbeing Index (PWI), and the Sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Two studies were conducted in each of these countries: Singapore [ 43 , 44 ], Hong Kong [ 45 , 46 ], Italy [ 47 , 48 ], The United States of America [ 49 , 50 ], Spain [ 51 , 52 ] and United Kingdom [ 53 , 54 ]. The remaining studies were conducted in Israel [ 55 ], India [ 56 ], South Korea [ 57 ], Malaysia [ 58 ], Thailand [ 59 ], Japan [ 60 ], Norway [ 61 ], Ethiopia [ 62 ], Chile [ 63 ] and China [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies were conducted in each of these countries: Singapore [ 43 , 44 ], Hong Kong [ 45 , 46 ], Italy [ 47 , 48 ], The United States of America [ 49 , 50 ], Spain [ 51 , 52 ] and United Kingdom [ 53 , 54 ]. The remaining studies were conducted in Israel [ 55 ], India [ 56 ], South Korea [ 57 ], Malaysia [ 58 ], Thailand [ 59 ], Japan [ 60 ], Norway [ 61 ], Ethiopia [ 62 ], Chile [ 63 ] and China [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were 44 365 subjects included from the 27 studies (see S1 Table ) with a sample size ranged between 40 and 15 321. Only seven studies reported the mean age of the participants, which range from 28.17 to 43.60 years [ 43 , 44 , 50 , 53 , 56 , 59 , 64 ] Out of 24studies that reported on gender composition, 13 studies had more female participants while another 11 studies had more male participants. Five studies did not state any information on the gender composition of their participants [ 43 46 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al [ 22 ] analyzed the potential psychological mechanisms of subjective well-being in migrant workers using structural equation models. The investigators randomly recruited 2573 migrant workers from Shanghai.…”
Section: The Work Includedmentioning
confidence: 99%